2015
DOI: 10.1007/s12026-015-8700-y
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 restricts dendritic cell (DC) growth at the monocyte-to-monocyte-derived DC interface by disrupting anti-apoptotic and cytoprotective autophagic molecular machinery

Abstract: An evolving premise is that cytoprotective autophagy responses are essential to monocyte-macrophage differentiation. Whether autophagy functions similarly during the monocyte-to-dendritic cell (DC) transition is unclear. IL-10, which induces apoptosis in maturing human DCs, has been shown to inhibit starvation-induced autophagy in murine macrophage cell lines. Based on the strict requirement that Bcl-2-mediated anti-apoptotic processes are implemented during the monocyte-to-DC transition, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…These data suggest that activated B cells/plasma cells can promote the formation of CD11c+ cells in an IL-10 independent manner, at least in vitro . Though it is known that IL-10 inhibits cytoprotective mechanisms in monocyte derived DC leading to increased apoptosis (27), the mechanism of how activated B cells/plasma cells promote the generation of DC remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that activated B cells/plasma cells can promote the formation of CD11c+ cells in an IL-10 independent manner, at least in vitro . Though it is known that IL-10 inhibits cytoprotective mechanisms in monocyte derived DC leading to increased apoptosis (27), the mechanism of how activated B cells/plasma cells promote the generation of DC remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, this cytokine was shown to control monocyte differentiation to macrophages during peritoneal infection in mice (26). Moreover, IL-10 has been reported to restrict the growth of monocyte-derived DCs by the inhibition of cytoprotective autophagy leading to increased apoptosis (27). Several studies indicate that age-related changes in IL-10 production of various cell populations contribute to the age-related chronic progressive increase in the proinflammatory status, sometimes referred to as “inflammaging,” and changes of immune responses in older individuals (2832).…”
Section: Introductionmentioning
confidence: 99%
“…During monocytes–DCs differentiation and DCs survival, cytoprotective autophagy responses are essential for counteracting IL-10-triggered apoptosis, but IL-10 can strongly inhibit starvation-induced autophagy and decrease Bcl-2 levels, which indicates increased levels of Beclin-1, LC3, and mature autophagosomes and results in restricting DCs growth. IL-10 not only kills nascent antigen-presenting DCs but also specifically skews the growth of DCs toward non-antigen-presenting monocytes–macrophages, and the autophagy inhibitor 3-methyladenine(3-MA) restricted DCs differentiation by prompting apoptosis [138] . Celastrol has been reported to ameliorate colitis in IL-10 deficient mice, which has clearly confirmed that celastrol up-regulated the autophagy of colon tissue in IL-10−/− mice by inhibiting the PI3K/Akt/mTOR signaling pathway.…”
Section: The Relationship Between Autophagy and Cytokinesmentioning
confidence: 99%
“…According to the present data, mice can recover because autophagy is involved in the phagocytosis of dead cells. Clearance of the apoptotic cells by phagocytes plays an important role in the maintenance of tissue homeostasis as well as the promotion of immunological tolerance and the antiinflammatory response [20,21]; however, the contribution of autophagic destruction of apoptotic cells by macrophages or other cells is not well defined.…”
Section: Discussionmentioning
confidence: 99%